ANALISIS IMPLEMENTASI UU NO. 14 TAHUN 2005: DAMPAK SERTIFIKASI TERHADAP KINERJA DOSEN DAN GURU PAI - M Arief Rahman; Titi Kadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The educator certification policy in Indonesia is one of the most significant educational reform milestones since the beginning of the reform era, which is juridically contained in Law Number 14 of 2005 concerning Teachers and Lecturers. The main problem raised in this study is the gap between the ideal goal of certification, namely improving the quality of learning and educator competence and the reality of the field, which often shows that the impact of certification is more dominant on the aspect of financial welfare than on substantive performance improvement. The purpose of this study is to critically evaluate the effectiveness of the implementation of the national policy, especially for educators in the field of Islamic Religious Education (PAI) who bear moral and spiritual responsibilities in shaping the nation's character. Methodology that uses a qualitative-descriptive approach with literature study techniques, analysis of policy documents, and synthesis of various results of previous field research. Furthermore, the results found in this study show that certification has a positive and significant impact on the work motivation and economic welfare of PAI lecturers and teachers through the Teacher Professional Allowance (TPG). However, the impact on pedagogic competence and professionalism is still hampered by high administrative burdens, lack of post-certification continuous training, and limited supporting infrastructure in various regions. This research also found that there is a crisis in the Teacher Professional Education (PPG) quota that threatens to accelerate the standardization of PAI teacher professionalism ahead of the target of closing the program in 2025.